Mental disorders, multimorbidity and labor market marginalization among refugee youths in Sweden. (20th October 2021) - Chen, J; Mittendorfer-Rutz, E; Klimek, P
Abstract: Background: Little is known about how disease co-occurrences with common mental disorders (CMD) associate with social integration in young refugees. We identify diagnostic groups associated with labor market marginalization (LMM) in refugees and Swedish-born with CMD and determine whether multimorbidity is associated with LMM in young refugees and Swedish-born with CMD. Methods: This longitudinal registry-based study included adults aged 20-25 years followed from 2011-2016 in Sweden. LMM was defined as > 180 days unemployment or being granted disability pension. A multimorbidity score was derived from a network of disease co-occurrences observed in 2009-2011. Relative risks for LMM in refugees with CMD compared to Swedish-born with CMD in 114 diagnostic groups were calculated. Multivariate logistic regression was applied to estimate the odds of LMM by CMD. Results: Among 249, 245 young adults, 2, 841 (1.1%) were granted disability pension and 16, 323 (6.5%) individuals experienced unemployment, 20, 679 (8.3%) suffered from CMD. Most comorbid diagnostic groups were positively associated with unemployment in young refugees with CMD. Inflammatory bowel disease and acute upper respiratory disease showed the highest relative risks of unemployment for young refugees with CMD, compared to Swedish-born with CMD: RRs 6.4[3.2, 12.8], 4.0[2.6, 6.1], respectively. The multimorbidity score was associated with elevated odds for unemployment and granted disability pension in refugees with/without CMD and Swedish-born with/without CMD (OR range: 1.1-1.8; highest for young refugees without CMD). Conclusions: Specific diagnostic group had differential risks for unemployment for refugees and Swedish-born. Early culturally sensitive public health measures are warranted to target the detrimental consequences of multimorbidity on LMM in young adults. Key messages: The importance of diagnostic groups for LMM differs for young refugees and Swedish-born with CMD. Multimorbidity increases the risk for LMM, particularly disability pension.